PENGARUH FAKTOR FUNDAMENTAL PADA SIKLUS HIDUP PERUSAHAAN TERHADAP RETURN SAHAM - Wizanasari Wizanasari (Universitas Pamulang, 2019)
The objective of this research is to re-examine the effect of fundamental factor and life cycle of firms to return stock in manufacturing firms. The variables used in this research are price earning ratio (per), debt equity ratio (DER), return on equity (roe), return on assets (roa),return stock and life cycle of firms. The objective of this research are manufacturing companies listed in Indonesia Stock Exchange in the period 2009-2013. The sampling technique used in this research were purpose sampling, with some criteria, those where: (1) the manufacture company listed in JSX in research period and still operating consistenly in there search period; (2) the available of financial statement as the research period; (3) the manufacture company had not negative profit. Using multiple linear regression analysis and descriptive for the little sample.